Emerging Paradigms in Perioperative Management for Microsurgical Free Tissue Transfer. Issue 1 (January 2015) - Motakef, Saba; Mountziaris, Paschalia M.; Ismail, Inzhili K.; Agag, Richard L.; Patel, Ashit
<x xml:space="preserve">Abstract</x> Background: Microsurgical free tissue transfer has become an increasingly valuable technique in reconstructive surgery. However, there is a paucity of evidence-based guidelines to direct management. A systematic review was performed to define strategies to optimize perioperative management. Methods: A systematic review of the literature was performed using key search terms. Strategies to guide patient management were identified, classified according to level of evidence, and used to devise recommendations in seven categories: patient temperature, anesthesia, fluid administration/blood transfusion, vasodilators, vasopressors, and anticoagulation. Results: A total of 106 articles were selected and reviewed. High-level evidence was identified to guide practices in several key areas, including patient temperature, fluid management, vasopressor use, anticoagulation, and analgesic use. Conclusions: Current practices remain exceedingly diverse. Key strategies to improve patient outcomes can be defined from the available literature. Key evidence-based guidelines included that normothermia should be maintained perioperatively to improve outcomes (level of evidence 2b), and volume replacement should be maintained between 3.5 and 6.0 ml/kg per hour (level of evidence 2b). Vasopressors do not harm outcomes and may improve flap flow (level of evidence 1b), with most evidence supporting the use of norepinephrine over other vasopressors (level of evidence 1b). Dextran should be avoided (level of evidence 1b), and pump systems for local anesthetic infusion are beneficial following free flap breast reconstruction (level of evidence 1b). Further prospective studies will improve the quality of available evidence.